2010
DOI: 10.1016/j.jcmg.2009.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Fat Burden on ECG-Gated Noncontrast CT in Asymptomatic Patients Who Subsequently Experience Adverse Cardiovascular Events

Abstract: Background Pericardial fat volume (PFV) and thoracic fat volume (TFV) can be routinely measured from noncontrast CT (NCT) performed for calculating coronary calcium score (CCS) and may predict major adverse cardiovascular event (MACE) risk. Methods From a registry of 2751 asymptomatic patients without known CAD and 4-year follow-up for MACE (cardiac death, myocardial infarction, stroke, late revascularization) after NCT, we compared 58 patients with MACE (“EVENTS”) to 174 same-sex event-free controls matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
155
0
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(179 citation statements)
references
References 29 publications
12
155
0
12
Order By: Relevance
“…3 Notably, epicardial adipose tissue volume (EATV) measured by cardiac computed tomography (CT) is related to coronary plaque burden, 4 and is also significantly associated with cardiovascular events. 5, 6 Importantly, we recently demonstrated that adventitial inflammatory changes (eg, VV formation) are enhanced at the spastic coronary segment in patients with vasospastic angina (VSA), with a positive correlation with the extent of coronary vasoconstrictive responses. 7 Indeed, recent studies have suggested that coronary PVAT impairs coronary vasomotion, 8 but it remains to be elucidated whether coronary PVAT is altered in VSA patients.…”
mentioning
confidence: 99%
“…3 Notably, epicardial adipose tissue volume (EATV) measured by cardiac computed tomography (CT) is related to coronary plaque burden, 4 and is also significantly associated with cardiovascular events. 5, 6 Importantly, we recently demonstrated that adventitial inflammatory changes (eg, VV formation) are enhanced at the spastic coronary segment in patients with vasospastic angina (VSA), with a positive correlation with the extent of coronary vasoconstrictive responses. 7 Indeed, recent studies have suggested that coronary PVAT impairs coronary vasomotion, 8 but it remains to be elucidated whether coronary PVAT is altered in VSA patients.…”
mentioning
confidence: 99%
“…MDCT provides excellent delineation of pericardial anatomy of the entire chest, including the presence of any pericardial effusion, thickening or calcification. It also quantifies pericardial fat volume, a marker of cardiovascular disease 21,22 and may identify extra-cardiac lesions related to pericardial pathology.…”
Section: Pericardiummentioning
confidence: 99%
“…EAT mediates the inflammatory process within the atherosclerotic plaque (42). The paracrine or vasocrine secretion of epicardial inflammatory adipokines, such as tumor necrosis factor alpha, plasminogen activator inhibitor-1, interleukin-6, interleukin -1b, monocyte chemo-attractant protein-1, and resistin contribute to the metabolic and inflammatory milieu that promotes atherogenesis (43).…”
Section: Atherosclerosismentioning
confidence: 99%